Quantification of desloratadine in human plasma by LC-ESI-MS/MS and application to a pharmacokinetic study - Venkata Suresh Ponnuru; B.R. Challa; Ramarao Nadendla (Elsevier, 2012)
A simple, sensitive, and specific liquid chromatography tandem mass spectrometry (LC-MS/MS) method was developed for the quantification of desloratadine (DL) in human plasma using desloratadine-d5 (DLD5) as an internal standard (IS). Chromatographic separation was performed using an Xbridge C18 column (50Â mmÃ4.6Â mm, 5Â Î¼m) with an isocratic mobile phase composed of 10Â mM ammonium formate: methanol (20:80, v/v), at a flow rate of 0.7Â mL/min. DL and DLD5 were detected with proton adducts at m/z 311.2â259.2 and 316.2â264.3 in multiple reaction monitoring (MRM) positive modes, respectively. Liquidâliquid extraction (LLE) method was used to extract the drug and the IS. The method was validated over a linear concentration range of 5.0â5000.0Â pg/mL with a correlation coefficient of (r2)â¥0.9994. This method demonstrated intra- and inter-day precision within 0.7â2.0% and 0.7â2.7%, and an accuracy within 101.4â102.4%, and 99.5â104.8%. DL was found to be stable throughout the freezeâthaw cycles, bench-top, and postoperative stability studies. This method was successfully applied in the analysis of plasma samples following oral administration of DL (5Â mg) in 35 healthy Indian male human volunteers under fasting conditions. Keywords: Mass spectrometry, Desloratadine, Bioequivalence, Pharmacokinetic study